Penerapan Edukasi Kesehatan Diet Dash terhadap Kepatuhan Dan Tekanan Darah Pasien Hipertensi - Supriatun, Evi; Asyari, Hasim; Kayubi, Kayubi (Journal of Telenursing (JOTING), 2024)
This study aims to determine the influence of dietary approaches to stop hypertension (DASH) health education on dietary compliance and blood pressure in hypertensive patients located in the Kertasemaya Health Centre Working Area, Indramayu Regency. The research method used Quasi Experimental Pre-Post Test with Control Group by providing health education to the intervention group. Consecutive sampling was selected in sampling with inclusion criteria, namely 160-190 mmHg systole blood pressure, 90-100 mmHg diastole blood pressure, no disease complications, and adult age. The exclusion criteria for this study were those who did not participate in DASH diet health education activities and experienced cognitive impairment and conditions of decreased consciousness. The results showed that there were significant differences in dietary compliance, systole, and diastole blood pressure in the intervention group before and after provided DASH diet health education (p < 0,005). It is concluded that DASH diet health education affects dietary compliance and systole and diastole pressure of hypertensive patients. Keywords: DASH Diet, Hipertension, Diet Adherence, Blood Pressure